Ranko SIMILARITIES AND DIFFERENCES IN THE ISSUE OF SECURITIES AND CRYPTO-ASSETS - THE ISSUE OF LEGAL RESPONSIBILITY OF THE ISSUER - Sovilj, Ranko P. (Glasnik Advokatske komore Vojvodine, 2022)
The evolution of the financial market has given rise to new instruments of trade – crypto-assets. Having in mind the diversity and inhomogeneity of crypto-assets, the author analyzed the position of digital tokens, which, including their features, are compared to securities. Therefore, in the first part of the paper the author analyzes the issue of securities, primarily the issue of legal responsibility of the issuer for the lack of prospectus. On the other hand, in the second part of the paper author points out the issue of digital tokens, white paper content and the issuer’s responsibility for the white paper content. Hence, the aim of this research is to point out the similarities and differences that accompany the issuance of securities and digital tokens. Finally, using the normative and comparative method, the author concludes that despite the many advantages of legalizing the issuance and secondary trading of crypto-assets, the issuance of digital tokens is accompanied by risks and inequalities compared to the issuance of securities.